IMPLEMENTASI METODE BRAINSTORMING DALAM MODEL GROUP INVESTIGATION PADA MATA PELAJARAN EKONOMI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X IPS 3 SMAN 1 BATU - Yuni Tri Astuti; Agung Haryono (Jurnal Pendidikan Ekonomi, 2017)
The purpose of this research is to know the implementation of brainstormingmethod in group investigation model in Economic subjects and improvementof activity and learning result of students of class X IPS 3 SMAN 1 Batu.Methods of data collection using observation, test questions and field notesand analyzed by qualitative descriptive technique. The result of this researchare: (1) improvement of student activity 18,71% from cycle I to cycle II, thatis 63.30% cycle I and 82.31% cycle II; (2) the improvement of studentlearning outcomes is 22.22% from cycle I to cycle II, which is marked by theincrease of 70.37% complete student in cycle I and increased to 92.59%cycle II. Implementation of brainstorming method in group investigationmodel is expected to be used as an alternative model of economical learningthat is more innovative to improve student activeness. It is also expected thatEconomics teachers should implement the implementation of this learningmodel not only on the discussion of payment system and non-cash paymentinstruments only, but for other materials that have problems and materialsrelated to the daily life of the students so that students are easier to find thelatest information needed to be used as reference material. The results of thisstudy are expected to be used by other researchers as a reference in carryingout the development of similar research. In addition to measuring studentactivity as well as learning outcomes, other researchers are expected to beable to measure other aspects such as critical thinking skills, communicationskills, and so on, so that the results of research become more perfect. DOI: https://dx.doi.org/10.17977/UM014v10i22017p109